Construction of yeast microbial consortia for petroleum hydrocarbons degradation - Wang, Minzhen; Zhou, Mengyu; Li, Hengchang; Cao, Zhibei; Ding, Mingzhu; Yuan, Yingjin (Frontiers in Bioengineering and Biotechnology, 2024)
Microbial degradation of petroleum hydrocarbons plays a vital role in mitigating petroleum contamination and heavy oil extraction. In this study, a Saccharomyces cerevisiae capable of degrading hexadecane has been successfully engineered, achieving a maximum degradation rate of up to 20.42%. However, the degradation ability of this strain decreased under various pressure conditions such as high temperature, high osmotic pressure, and acidity conditions. Therefore, a S. cerevisiae with high tolerance to these conditions has been constructed. And then, we constructed an ‘anti-stress hydrocarbon-degrading’ consortium comprising en-gineered yeast strain SAH03, which degrades hexadecane, and glutathione synthetic yeast YGSH10, which provides stress resistance. This consortium was able to restore the degrada-tion ability of SAH03 under various pressure conditions, particularly exhibiting a significant increase in degradation rate from 5.04% to 17.04% under high osmotic pressure. This study offers a novel approach for improving microbial degradation of petroleum hydrocarbons.